Iron fist : classic armoured warfare case studies - Perrett, Bryan (London : Arms and Armour ; New York, NY : Distributed in the USA by Sterling Pub. Co., 1995)
"My intentions in writing this book ... have been to show how the vehicles themselves and the tactics employed were developed in the light of the crews' experience, and in so doing give the reader some impression of what the tactical tank battle looked like from the inside as it evolved over the years"--Introduction.
In the beginning -- War on wheels -- The land ironclads -- Blood on the tracks -- The Gembloux Gap and Flavion : the first tank battles of World War II -- Barbarossa : Raseiniai and Brody-Dubno, June 1941 -- Desert death-ride : Tel el Aqqaqir, 2-4 November 1942 -- War to the death : tank battles of the Russian Front, 1943/44 -- Hobo's funnies -- 'Hideous nights pressed on days of horror' : fighting in the Gothic Line, Italy, Autumn 1944 -- The armoured car in World War II -- Honour in adversity : holding actions on the road to Bastogne -- The Japanese dimension -- Above and beyond : individual achievements during the World Wars -- Red sheet : the Sinai campaign of 1967 -- The long war : Vietnam, 1946-1975 -- Green screen warfare : Operation Desert Sabre, Kuwait, February 1991.
Includes bibliographical references (pages 211-212) and index.
Keywords: 1900-1999; Tank warfare -- History